2016
DOI: 10.1002/cmdc.201600134
|View full text |Cite
|
Sign up to set email alerts
|

Rational Development of Novel Activity Probes for the Analysis of Human Cytochromes P450

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(40 reference statements)
0
4
0
Order By: Relevance
“… 114 Cravatt and co-workers have demonstrated that metabolic oxidation of alkynes can form ketene ( Figure 5 c) and α,β-unsaturated ketone electrophiles, 115 , 116 resulting in the labeling of a range of CYP enzymes. In 2016, Sutton and co-workers 117 extended this work by examining 8-hydroxypsoralen analogues that underwent CYP oxidation to form electrophilic furan epoxides ( Figure 5 d). The benzofuran probe JDS-14 was found to effectively inhibit CYP3A4 in enzymatic assays, and labeling of the overexpressed enzyme in cell lysate was also demonstrated.…”
Section: Endogenous Inductionmentioning
confidence: 99%
“… 114 Cravatt and co-workers have demonstrated that metabolic oxidation of alkynes can form ketene ( Figure 5 c) and α,β-unsaturated ketone electrophiles, 115 , 116 resulting in the labeling of a range of CYP enzymes. In 2016, Sutton and co-workers 117 extended this work by examining 8-hydroxypsoralen analogues that underwent CYP oxidation to form electrophilic furan epoxides ( Figure 5 d). The benzofuran probe JDS-14 was found to effectively inhibit CYP3A4 in enzymatic assays, and labeling of the overexpressed enzyme in cell lysate was also demonstrated.…”
Section: Endogenous Inductionmentioning
confidence: 99%
“…epoxyfuran, which would be electrophilic enough to be attacked by protein nucleophiles (Figure 3). [33] Probe 8 exhibited the most effective NADPH‐dependent binding to CYP3A4, which is also the most abundant P450 in the human body.…”
Section: Activity‐based Protein Profiling Of Various Oxidoreductasesmentioning
confidence: 99%
“…A P450 enzyme could convert the substrate into an epoxy‐furane, which would be electrophilic enough to be attacked by protein nucleophiles (Figure 1). [45] Probe 6 exhibited the most effective NADPH‐dependent binding against a panel of overexpressed CYP proteins to CYP3A4, which is also the most abundant P450 in the human body.…”
Section: Introductionmentioning
confidence: 99%